Militarisation of Space as a Domain of Warfare: An Indonesian Perspective - Setyawan, Irwan; Timur, F. G. Cempaka; Reksoprodjo, Agus Hasan S. (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2025)
The advancement of space technology and the growing acquisition of technology by various nations have transformed outer space into a new battlefield. This article explores the issue of militarization of space, concentrating on Indonesia's role within this context. Utilizing a qualitative research methodology through a literature review and S.W.O.T. analysis, the author assesses the strengths, weaknesses, opportunities, and challenges that Indonesia faces regarding space militarization. Despite notable progress in the development of space technology, Indonesia still encounters various challenges that need to be addressed at both national and international levels. Given the escalating global tensions surrounding the militarization of outer space, it is essential for Indonesia to effectively utilize its strengths and seize opportunities to bolster its capabilities in maintaining security in space.